2016
DOI: 10.1002/mar.20890
|View full text |Cite
|
Sign up to set email alerts
|

Employee Mere Presence and Its Impact on Customer Satisfaction

Abstract: Existing research suggests that humans are hardwired to be sensitive to the presence of other humans, and that the mere presence of someone is likely to affect human behavior. So far, however, this issue has been under-researched in physical environments in which retail and service transactions take place and with respect to the mere presence of employees. This study examined empirically if the mere presence of an employee in a physical environment has an impact on customer affect (in terms of pleasure) and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 83 publications
(116 reference statements)
9
34
0
Order By: Relevance
“…Two experiments are conducted with a total sample of 498 Chinese customers. Study 1, which involves a shopping situation in a clothing store, replicates Söderlund's () results and further reveals that employee mere presence has a significant positive impact on customers’ loyalty intentions. However, these results are reversed in Study 2, in which the shopping situation involves an embarrassing product (i.e., condom).…”
Section: Overview Of Studiessupporting
confidence: 69%
See 1 more Smart Citation
“…Two experiments are conducted with a total sample of 498 Chinese customers. Study 1, which involves a shopping situation in a clothing store, replicates Söderlund's () results and further reveals that employee mere presence has a significant positive impact on customers’ loyalty intentions. However, these results are reversed in Study 2, in which the shopping situation involves an embarrassing product (i.e., condom).…”
Section: Overview Of Studiessupporting
confidence: 69%
“…Their research focuses on shopping situations that take place in physical stores and other commercial settings where both customers and employees are likely to be present at the same time. This research attempts to replicate and extend Söderlund's () finding that customers entering a store with an employee present (vs. absent) shows higher levels of customer satisfaction. Two experiments are conducted with a total sample of 498 Chinese customers.…”
Section: Overview Of Studiesmentioning
confidence: 80%
“…To this end, two between‐subjects experiments with a total sample of 498 Chinese customers were conducted. Study 1, which involved a shopping situation in a clothing store, replicated Söderlund's () main results and further found that employee mere presence (vs. absence) had a significant positive impact on customers’ loyalty intentions. These results were reversed in Study 2, in which the shopping situation involved the purchase of an embarrassing product.…”
supporting
confidence: 66%
“…In fact, the authors are only aware of one recent research article (Söderlund, ) that has explicitly examined the isolated effect of employee mere presence on key customer outcomes. Söderlund () found that customers entering a store with an employee present (vs. absent) reported significantly higher levels of customer satisfaction, with their increased levels of pleasurable feelings mediating this effect. However, similar to the majority of theorizing on customer satisfaction, which has been conducted in Europe and North America, Söderlund's research was restricted to data collected in a Western and individualistic society (Scandinavia)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation